Fungsi Bregada Musik pada Upacara Grebeg Karaton Surakarta - Ade Ksatria Wanadri; Iwan Budi Santoso (Universitas Negeri Medan, 2026)
This study examines the function of the music brigade in the Grebeg ceremony of the Surakarta Palace using Alan P. Merriam's Uses and Functions of Music theory. The music brigade is understood as a unit of musical soldiers present in Grebeg Maulud, Grebeg Syawal, and Grebeg Besar, which have similar functions and procession structures. The study used a qualitative descriptive method through direct observation, interviews, and field data analysis. The results of the study indicate that the music brigade not only plays a role as an accompaniment to the procession, but also carries out social, symbolic, and ritual functions. Music functions as a communication medium to provide cues for the stages of the procession, an expression of collective emotions, a driver of physical responses, a reinforcement of social norms, community integration through sound as a marker of the procession, and a symbolic representation of the power and greatness of the Surakarta Palace. The implementation of the music brigade takes place in three stages, namely the preparation of soldiers, respect and the procession journey, and completion at the destination of the ceremony. These findings confirm the position of the music brigade as a key element that regulates, enlivens, and gives meaning to the course of the traditional Surakarta ceremony.